Makna Loyalitas Konsumen Terhadap Produk Kopi Lokal Di Makassar: Sebuah Pendekatan Fenomenologi - Azhari, Azlan (Politeknik Sawunggalih Aji, 2025)
This study explores the meaning of consumer loyalty toward local coffee products as a social and emotional phenomenon deeply rooted in the cultural context of Makassar society. Employing a qualitative phenomenological approach, twelve active local coffee consumers in Makassar participated in in-depth interviews to reveal how loyalty is perceived, experienced, and constructed in their everyday lives. Thematic analysis was conducted to identify the essential structures shaping consumers’ lived experiences of loyalty. The findings reveal four major dimensions: (1) emotional attachment through taste and atmosphere, (2) loyalty as an expression of social identity, (3) togetherness and the sipulung value within coffee communities, and (4) pride in local products as a symbol of authenticity. The study demonstrates that consumer loyalty is not merely driven by product quality but is rooted in social meanings, cultural values, and emotional connections cultivated through shared experiences in local coffee spaces. Theoretically, this research expands the understanding of consumer loyalty by positioning it as a phenomenological construct that integrates emotional, social, and cultural dimensions. Practically, the findings offer insights for local coffee entrepreneurs to design marketing strategies grounded in value, authenticity, and local cultural narratives that foster long-term emotional bonds with consumers.